Combination of double‐modified clay and polypropylene‐graft‐maleic anhydride for the simultaneously improved thermal and mechanical properties of polypropylene. Issue 1 (27th June 2012) - Xu, Yuanyuan; Guo, Zhenghong; Fang, Zhengping; Peng, Mao; Shen, Lie
Abstract Double‐modified montmorillonite (MMT) was first prepared by covalent modification of MMT with 3‐aminopropyltriethoxysilane and then intercalation modification by tributyl tetradecyl phosphonium ions. The obtained double‐modified MMT was melt compounded with polypropylene (PP) to obtain nanocomposites. The dispersion of the double‐modified MMT in PP was found to be greatly improved by the addition of PP‐graft‐maleic anhydride (PP‐g‐MA) as a "compatibilizer, " whose anhydride groups can react with the amino groups on the surface of the double‐modified MMT platelets and thus improve the dispersion of MMT in PP. Fourier transform infrared, X‐ray diffraction, transmission electron microscopy, thermogravimetric analysis, scanning electron microscopy, and tensile test were used to characterize the structure of the double‐modified MMT, morphology, and the thermal and mechanical properties of the nanocomposites. The results show that PP‐g‐MA promotes the formation of exfoliated/intercalated morphology and obviously increases the thermal properties, tensile strength, and Young's modulus of the PP/double‐modified MMT nanocomposites. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013